Effects of fuel ratio on performance and emission of diesel-compressed natural gas (CNG) dual fuel engine - Ismail, M. M.; Fawzi, M.; Zulkifli, F. H.; Osman, S. A. (Society of Automotive Engineers Malaysia, 2018)
Recent research breakthrough reveals that diesel-CNG dual fuel (DDF) combustion can potentially reduce exhaust emission of internal combustion engines. However, problem arises when knock phenomenon occurs producing high carbon monoxide (CO) and hydrocarbon (HC) emission due to uncontrolled blending ratio of diesel-CNG fuel on specific engine load. This study will determine the limit of dual fuel ratio before knock occurrence while analysing performance and exhaust emission of an engine operating with diesel and DDF fuel mode. A 2.5 litre 4-cylinder direct injection common-rail diesel engine was utilised as a test platform. The modelstested were 100% Diesel, 90% DDF, 80% DDF and 70% DDF, representing diesel to CNG mass ratio of 100:0, 90:10, 80:20 and 70:30 respectively. It was found that DDF engine performance was lower compared to diesel engine at 1500 rpm engine speed. At higher engine speed, the 70% DDF showed engine performance comparable to diesel engine. However, high HC emission with knock onset and a decrease of Nitrogen Oxide (NOX) emission were recorded. This study suggests the preferred limit of dual fuel ratio should not be lower than 70% DDF which will be able to operate at high engine speed without the occurrence of knock and poor exhaust emission.